Alkylation of quinoxalin-2(1H)-ones using phosphonium ylides as alkylating reagents. Issue 44 (2nd November 2021) - Peng, Sha; Liu, Jun-Jia; Yang, Luo
Abstract : A practical and efficient protocol for the preparation of 3-alkylquinoxalinones through base promoted alkylation of quinoxalin-2(1 H )-ones with phosphonium ylides under metal- and oxidant-free conditions was developed. Abstract : A practical and efficient methodology for the construction of 3-alkylquinoxalinones through base promoted direct alkylation of quinoxalin-2(1 H )-ones with phosphonium ylides as alkylating reagents under metal- and oxidant-free conditions was developed. Various 3-alkylquinoxalin-2(1 H )-ones were easily obtained in good to excellent yields. Tentative mechanistic studies suggest that this reaction is likely to involve a nucleophilic addition–elimination process.